Pharmacodynamic effects of antibiotics and antibiotic combinations on growing and nongrowing Staphylococcus epidermidis cells. - Svensson, E (1997)
The pharmacodynamic effects of amikacin, imipenem, ofloxacin, rifampin, and vancomycin were studied on the slime-producing, oxacillin-resistant strain Staphylococcus epidermidis ATCC 35984 growing in Mueller Hinton broth or, in order to inhibit growth, incubated in phosphate-buffered saline. The investigated parameters were postantibiotic effect (PAE) and control-related effective regrowth time (CERT), which were determined by bioluminescence assay of bacterial ATP. PAE describes the delayed regrowth after drug removal, and CERT describes the combined effects of initial change in bacterial density during antibiotic exposure and delayed regrowth after drug removal. In growth cultures, PAE and CERT were drug concentration dependent for all antibiotics. The length of the PAE and CERT in the growing cultures were as follows: ofloxacin > rifampin > amikacin > vancomycin > imipenem. Imipenem combined with amikacin and vancomycin, respectively, induced a synergistic effect against growing cultures. In nongrowing cultures rifampin was the only drug that induced strong concentration-dependent effects. The combination of drugs induced no synergistic effects against nongrowing bacteria.